Professional Competence of Graduates from Higher and Secondary Special Educational Institutions in Context of Continuous Education - M. G. Sergeyeva (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The problem of professional competence of young specialists who have graduated from higher and secondary special educational institutions in the conditions of continuous education is considered. The study focuses on economic education, which is due to the scientific specialization of the first author of the article. According to the authors, the negative results of the majority of economic reforms carried out in our country are determined by the lack of preparedness of the main part of citizens to a new stage of social development, lack of awareness about the basic economic phenomena and laws of social life. The relevance of the chosen topic is related to the role of the federal state educational standards of the third generation, the features of which are analyzed in this work after the review of the key concepts of continuing education: “competence,” “competency” and “professional competence.” The practical part describes the basis of the author’s concept of economic competence of students: a brief description of the economic competencies included in its structure, and their respective levels of professional education (basic, professional, auxiliary). It is noted that the distinguished levels imply a competent change of stages of economic education while maintaining such characteristics of professional education as integrity, openness to all verifiable aspects of human knowledge and reliance on previous intellectual and moral experience.